Cambridge English Empower Upper Intermediate : Student's Book : B2 - Thaine, Craig; Doff, Adrian; Puchta, Herbert, 1951-; Stranks, Jeff; Lewis-Jones, Peter; Godfrey, Rachel; Cambridge English Language Assessment (Organisation) (Cambridge : Cambridge University Press, 2015)
Upper Intermediate Presentation Plus provides the complete Upper Intermediate Student's Book content and the Workbook content with built-in annotation tools, embedded audio, and class video in an easy-to-operate format for interactive whiteboards or computers and projectors
"Cambridge English Language Assessment, Part of the University of Cambridge."
Keywords: English language -- Textbooks for foreign speakers